Forming networks between rural schools and their local areas: shared projects and their impact in the Asturian context - del-Moral-Pérez, María Esther; L´`ópez-Bouzas, Nerea; Castañeda-Fernández , Jonathan; Neira-Piñeiro, María del Rosario (Theory & Practice in Rural Education, 2024)
Rural schools play an important role in their local areas, helping stimulate the community and promoting activities with economic, social, and cultural impact on the area. This study aimed to identify the projects undertaken by 44 rural schools in Asturias (Spain) in collaboration with local agents and organizations by consulting the school management teams. It also sought their opinions about the impact of these projects. The study used a mixed methodology: quantitative, analyzing the data collected from a semi-open questionnaire, and qualitative, listing and describing the projects. The questionnaire included questions about the organizations the schools collaborated with, the goals and subjects of the shared projects, and funding sources, and it asked for their opinions about their impact. The results indicate that rural schools in Asturias have undertaken projects covering various subjects in collaboration with local authorities, cultural centers, libraries, public health centers, small businesses, and On-Governmental Organizations (NGOs). The respondents were very satisfied with the activities. They viewed their schools as a stimulus for their areas, stating that the projects encouraged a sense of belonging to the area and helped construct a collective identity. They also felt that they responded to shared needs, offered services to the community, allowed people to settle or remain in the area, and, to a lesser extent, helped local businesses and the local economy. Finally, the study concludes that these schools play an active role in their local areas, and highlights the importance of external support to implement initiatives that benefit the rural population.